Radical Incrementalism: An Open Letter in Defense of the Small - Dan Etheridge; Emilie Taylor (Oz, 2013)
Dear Urban Change Agent, We know you have big ideas, we do too. You think good design can make a difference. You see the work of others in the world, folks like Rural Studio, MASS, or the Center for Urban Pedagogy and you think, my community has needs and opportunities that could be addressed by design.